Effects of subsurface drip fertigation on potato growth, yield, and soil moisture dynamics - Zhao, Guoqiang; Luo, Xianxin; Wang, Zhan; Sheng, Gang; Liu, Wei; Wang, Yueming (Frontiers in Sustainable Food Systems, 2024)
Aims This study aimed to evaluate the impact of subsurface drip fertigation (SDF) on soil moisture content, potato growth, and tuber yield in loam soils, and compare these results with conventional surface drip fertigation (CF). The focus was on determining whether SDF could improve water use efficiency and yield quality, particularly in water-scarce regions. Methods The experiment was conducted during the 2022 spring growing season in Xunyang, Ankang, Shaanxi Province, China. A randomized complete block design (RCBD) was used with three treatments: subsurface drip fertigation (SDF), conventional surface drip fertigation (CF), and a no-fertilization control (NF), with four replications per treatment. Soil moisture content at a 20 cm depth was monitored, and plant growth parameters such as plant height, stem diameter, leaf color index, and chlorophyll fluorescence index were measured during the flowering and harvest stages. Tuber yield characteristics, including tuber diameter, number of tubers per plant, total yield, and marketable yield, were also assessed. Important findings The results indicated that subsurface drip fertigation significantly improved soil moisture content, with up to 45.5% higher moisture retention compared to conventional fertigation, particularly in the early stages of fertilization. This improved moisture availability led to enhanced plant growth and tuber development. Tuber diameter increased by 6.9 mm, and the number of tubers per plant increased by 18.1% under SDF. Marketable tuber yield was approximately 10% higher in the SDF treatment compared to CF. However, the study found that soil texture plays a critical role in the effectiveness of SDF, and further research is needed to explore its application in other soil types.